2016
DOI: 10.1039/c6tc01250g
|View full text |Cite
|
Sign up to set email alerts
|

A highly stable rhenium organosol on a DNA scaffold for catalytic and SERS applications

Abstract: A highly stable Re0 organosol on a DNA scaffold has been synthesized for the first time and tested for two different potential applications such as in the catalytic reduction of hexavalent chromium ions and in SERS studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 62 publications
3
39
0
1
Order By: Relevance
“…The UV‐visible absorption spectrum of an aqueous solution of pure DNA exhibited a predominant peak at λ max =260 nm resulting from the absorption of the aromatic bases present in the backbone of the DNA (Figure ) ,,. The absorption spectrum of the aqueous solution of the Rh/DNA was very similar to that of pure DNA with the absorption band only slightly shifted.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The UV‐visible absorption spectrum of an aqueous solution of pure DNA exhibited a predominant peak at λ max =260 nm resulting from the absorption of the aromatic bases present in the backbone of the DNA (Figure ) ,,. The absorption spectrum of the aqueous solution of the Rh/DNA was very similar to that of pure DNA with the absorption band only slightly shifted.…”
Section: Resultsmentioning
confidence: 93%
“…A new DNA‐based asymmetric Diels‐Alder,,, Friedel‐Crafts, or other C–C bond forming reactions, yielding desired products with 99% or 93% ee, have been performed by utilizing a DNA‐copper catalyst. DNA was also used to stabilize metal nanoparticles such as Rh,, Pt,, Fe, Au,,, Ag,, Pd,, or Re ,…”
Section: Introductionmentioning
confidence: 99%
“…The SERS study on detecting MB using such hybrids also demonstrated a high enhancement factor of 2.07 × 10 7 . The same research group later synthesized ultra-small ReNPs in an organosol, where the mixture of NH 4 ReO 4 and DNA was first transferred from the aqueous phase to the organic phase using tetraoctylammonium bromide (TOAB) as a phase transfer catalyst under freezing conditions and then reduced by NaBH 4 [175]. Yurkov et al [41] employed a thermal decomposition approach to synthesize Re-polyethylene (Re@PE) nanocomposites.…”
Section: Rhenium-based Nanocompositesmentioning
confidence: 99%
“…It works, when the incident light hits on rough metal surface adsorbed on the probe molecule gets increased Raman signal in a few orders of magnitude [7,8]. The noble metal-based nanomaterials (NMs) such as Ag [9], Au [10], Pt [11], Pd [12], Re [13], Os [14], Ir [15], and RuO 2 [16] having the remarkable surface plasmon resonance (SPR) nature in the visible region. Many factors that are influencing the enhancement of such SERS signal mainly, wavelength, polarization, and incidence angle of the laser light [17][18][19].…”
Section: Introductionmentioning
confidence: 99%